The Effect of Blended Learning Model and Higher Order Thinking Skills on Students' Learning Achievement - Gunawan, Guntur; Sapri, Johanes; Hadiwinarto, Hadiwinarto; Yumiarty, Yuyun (Tarbawi : Jurnal Ilmu Pendidikan, 2022)
The traditional learning model makes students only spectators and listeners, so the learning process becomes passive. Limited time is also causing a lack of students' absorption of the material presented. The purpose of this study was to compare student learning outcomes that use a blended learning model and the traditional learning model. This study used a quasi-experimental approach with a nonequivalent factorial pretest-posttest control group design. The instruments to collect data included tests of higher-order thinking skills and learning achievement tests. The results of the study show that the blended learning model has a significant influence on student achievement in Islamic Religious Education subject. There is a sizable difference in student achievement between the experimental group and the control group. This research perhaps helps lecturers understand how to apply blended learning.